Effect of Different Sources of Zinc on Growth Performance and Hemato-Biochemical Profiles in Murrah Buffalo Calves - Kumar, Atul; Sahu, DS; Chandra, Gulab; Yadav, SP; Kumar, Raj; Jaiswal, Vikas; Maurya, Premsagar; Singh, Rakesh Kumar (Indian Journal of Animal Nutrition, 2018)
Eighteen 12-15 months old buffalo calves were used to compare the effects of inorganic and organic zinc (Zn) supplements on growth performance, hemato-biochemical profile. Calves provided three diets in a randomized block design: basal diet with no supplemental Zn (control), basal diet plus 40 mg Zn/kg dry matter as zinc sulfate hepthydrate (ZS) and basal diet plus 40 mg Zn/kg dry matter as zinc methionine (ZM) for 90 days. Body weight and feed consumption were not significantly different between treatments. Body weight gain (BWG) was higher (P